The ghost belonged to me a novel - Peck, Richard 1934- (New York Viking Press, 1975)
In 1913 in the Midwest a quartet of characters share adventures from exploding steamboats to "exorcizing" a ghost.
Keywords: Ghosts -- Fiction; Middle West -- Fiction